IMPLEMENTASI MANAJEMEN PEMBELAJARAN DALAM PENINGKATAN PRESTASI BELAJAR SISWA SMA AL FALAKHUSSA’ADAH WAY KANAN - Muhamad Komarudin; Tamyiz; Rita Linda (UNISAN JURNAL, 2022)
Based on preliminary research, the process of managing learning activities that begins with planning, organizing, directing or controlling activities, and assessments at Al Falakhussa'adah Way Kanan High School goes as usual, nothing seems different. However, when viewed from academic and non-academic achievements, Al Falakhussa'adah Way Kanan High School students are classified as good, even though they have only graduated two batches. This type of research is descriptive qualitative research. The data sources are all teachers, principals, representatives and students of Al Falakhussa'adah Way Kanan High School. Data collection techniques used are observation, interviews and documentation. The data analysis techniques used were qualitative analysis techniques, with the following steps: categorizing data, reducing data, presenting data and classifying data according to the research focus and then drawing conclusions from the data obtained in this study. The results showed that the implementation of Learning Management in SMA Al Falakhussa'adah Way Kanan went through planning, organizing, directing and assessing activities. Each stage is carried out with good criteria by the Al Falakhussa'adah Way Kanan High School teacher. However, based on the results of data analysis, it was revealed that research findings that provide answers to the formulation of the research problem were revealed. In planning activities, teachers must, with superior control, prepare and develop their creativity so that the results are effective and efficient. In organizing and directing activities, each class is guided by two teachers with the number of students in each group of no more than 28 people, so that learning is more effective. In addition, learning activities are supported by complete facilities and are organized on a one for all basis, all available under one school roof. Keywords: Implementation, Management, Learning Improvement